Exposing Students to Industrial Experience through Workplace Exposure Project for Business Communication (LSP International Journal, 2018)
This paper aims to describe the implementation of a business communication project called Workplace Exposure Project (WEP). The project involved 36 students requiring them to have an industrial site visit (s) and conducting a semi-structured interview as well as observation. Students were required to find out about business communication practices employed by the chosen company and to write their reflections before, during and after the WEP. Prior to the WEP, they had to obtain permission from relevant parties in order to gain entry into the organisation. Finally, the students had to present their findings to the class orally and submit a written portfolio. Through their reflections, it was indicated that the students enjoyed the learning process using this method as it exposed them to real industrial experience of having an encounter(s) with people from a real business entity and giving them the opportunity and confidence to practice their English language skills. Concurrently, the university was also able to identify the performance of the students as perceived by the employers/business owners. The paper concludes with teaching implications for business communication and suggestions for future research.